Early-Life Exposure to Sex Hormones Promotes Voluntary Ethanol Intake in Adulthood. a Vulnerability Factor to Drug Addiction. - Renard, G (Elsevier Inc., 2024)
While there is extensive research on alcohol dependence, the factors that make an individual vulnerable to developing alcoholism haven t been explored much. In this study, we aim to investigate how neonatal exposure to sex hormones affects alcohol intake and the regulation of the mesolimbic pathway in adulthood. The study aimed to investigate the impact of neonatal exposure to a single dose of testosterone propionate (TP) or estradiol valerate (EV) on ethanol consumption in adult rats. The rats were subjected to a two-bottle free-choice paradigm, and the content of dopamine (DA) and 3,4-dihydroxyphenylacetic acid (DOPAC) in the nucleus accumbens (NAcc) was measured using HPLC-ED. The expression of critical DA-related proteins in the mesolimbic pathway was evaluated through RT-qPCR and western blot analysis. Supraphysiological neonatal exposure to EV or TP resulted in increased ethanol intake over four weeks in adulthood. In addition, the DA and DOPAC content was reduced and increased in the NAcc of EV and TP-treated rats, and β-endorphin content in the hypothalamus decreased in EV-treated rats. The VTA μ receptor and DA type 2 form short receptor (D2S) expression were significantly reduced in EV and TP male rats. Finally, in an extended 6-week protocol, the increase in ethanol consumption induced by EV was mitigated during the initial two hours post-naloxone injection. Neonatal exposure to sex hormones is a detrimental stimulus for the brain, which can facilitate the development of addictive behaviors, including alcohol use disorder. © 2023